Impact of a medication therapy management service offered to patients in treatment of breast cancer - Pedro Augusto do Amaral; Simone de Araújo Medina Mendonça; Djenane Ramalho de Oliveira; Leonardo José Peloso; Reginaldo dos Santos Pedroso; Maria Ângela Ribeiro (Universidade de São Paulo, 2018)
ABSTRACT Cancer has high morbidity and mortality rates related to medication use and produce a costly impact in health care. Thus, patients require constant monitoring and proper coordination of care between different professionals. This study aimed to evaluate the impact generated by a Medication Therapy Management service (MTM) offered to patients with breast cancer in use of polypharmacy. Observational, exploratory, descriptive and retrospective study of a MTM service that included 93 patients. Sociodemographic and clinical data related to pharmacotherapy and the processes associated with the systematization of the service were collected and analyzed. Patients were followed-up by the MTM service on average for 18 months (±4.31) and 185 drug-related problems (DRP) were identified, an average of two DRP per patient. Of these DRP, 48.11% were resolved and 49.73% were in the resolution process. The most common DRP were in the categories of Indication (37.84%), followed by Safety (23.78%). The safety category showed the highest resolution rate (59.09%). The study revealed an increased risk of DRP for patients with three or more comorbidities and using 5 or more medications. The process of systematization of a MTM service in oncology was associated with positive outcomes.